Impactos da pandemia do Covid-19 sobre a atuação das bibliotecas das Unidades Acadêmicas do Setor Norte da UFAM - Almeida, Anna Karoline Lima de (Brasil, 2022)
It presents the results of the study developed on the impacts of the Covid-19 Pandemic on the performance of Sector Libraries in the North Sector of the Manaus Campus of the Federal University of Amazonas – UFAM, especially the Sectoral Library of the North Sector, of the Sectoral Library of the Faculty of Law and the Library of the Faculty of Exact Sciences and Engineering. It also reflects on the measures adopted by the Central Library and these Libraries after the suspension of face-to-face work by the UFAM Rectory, in compliance with the guidelines of the social distancing protocol prepared by the World Health Organization (WHO) and adopted by the Ministry of Health for application throughout the national territory. Descriptive in nature, the study aimed to understand the repercussions of the measures adopted by these libraries, after the suspension of face-to-face work by the UFAM Rectory, to continue working even during the Covid-19 Pandemic. Regarding the methodological procedures, bibliographical and field research were carried out. The first to select the theoretical contributions that guided the analysis of the information obtained in the collection stage and the second to apply the instruments (questionnaires), which were prepared in Google Forms and applied to the Central Library manager and to five BSCEE Librarians, BSFD and BSSN. As for the results of the study, there were occurrences that attest that the studied libraries responded positively to the challenge of keeping operating even after the suspension of their in-person activities. Among these, the most significant was the transition from face-to-face work to the home office, as all other actions supported by current communication and information technologies were derived from it, such as: the development of information source guides, use and maintenance of profiles on networks social networks to interact with the academic community and to disseminate services, training, webinars, in order to meet the needs and demands of users even at a distance.